A nationwide trend analysis on the usage of endomyocardial biopsy - Keller, Karsten; Göbel, Sebastian; Gori, Tommaso; Münzel, Thomas; Wenzel, Philip; Hobohm, Lukas (Clinical cardiology, 2024)
Background Endomyocardial biopsy (EMB) is a safe procedure performed in diagnostic work-up of cardiac disease.Hypothesis Data regarding temporal trends of total numbers, characteristics, in-hospital outcomes, and complications of patients undergoing EMB are sparse.Methods The nationwide German inpatient sample (2005-2019) was used for this analysis. Patient cases of EBM during the 5-year cycles from 2005 to 2009, 2010 to 2014, and 2015 to 2019 were compared, and temporal trends regarding total numbers and presumable major and minor EMB-associated complications were investigated.Results Overall, 67 745 EMB were performed in Germany 2005-2019. Total number of EMB increased from 3083 in 2005 to 5646 in 2019 (beta 0.40 [95% confidence interval [CI] 0.37-0.43], p < .001). Among these EMB, 19 083 (28.2%) were performed during the period 2005-2009, 22 867 (33.7%) 2010-2014, and 25 795 (38.1%) between 2015 and 2019. The proportion of patients aged >= 70 years was highest 2015-2019 (2005-2009: 9.3%; 2010-2014: 13.8%; 2015-2019: 16.1%, p < .001) and the most aggravated comorbidity profile (Charlson Comorbidity Index 2.25 +/- 1.93; 2.67 +/- 2.14; 3.01 +/- 2.29, p < .001) was also detected 2015-2019. Major complications occurred less often in the period 2015-2019 compared to 2005-2009 (odds ratio [OR] 0.921 [95% CI 0.893-0.950], p < .001), whereas minor complications were more frequently observed between 2015 and 2019 (OR 1.067 [95% CI 1.042-1.093], p < .001). While a decrease in major complications was detected irrespective of age, an increase in minor complications was identified only in patients between 30-59 years.Conclusions Annual numbers of EMB increased significantly in Germany 2005-2019. Patients who underwent EMB in recent years were older and showed an aggravated comorbidity profile accompanied by fewer major complications, underscoring safety of the procedure.
Gesehen am 09.04.2024